Implementasi Aplikasi Genesys dalam Bisnis Properti: Analisis Etnografi di PT WR (Badan Usaha Milik Negara) dan PT PI (Perusahaan Swasta) - Rahmi, Mutia; Heikal, Jerry; Dzulqornain, Muhammad; Osthar, Fidy Rachman (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study investigates the implementation of the Genesys application as an integrated system in the property business sector, focusing on two companies with distinct organizational types: PT WR (a state-owned enterprise) and PT PI (a private company). Employing a qualitative method with an ethnographic approach, data were collected through in-depth interviews, life histories, and document analysis. The study examines the reasons behind the system transition, the duration and process of implementation, the obstacles encountered, and the users’ experiences. Results indicate that PT WR completed implementation within six months, while PT PI required 14 months due to assumptions about standardized needs and internal adaptation delays. Challenges included system migration, lack of customization, and limited familiarity among certain departments, such as tenant relations and accounting. Management responses differed: PT WR initially switched to another system (Propertex) before returning to Genesys, while PT PI opted for continuous training and system adjustments in collaboration with the Genesys team. Ultimately, both companies experienced improvements in financial reporting, bank reconciliation, automated billing, tax invoice processing, and communication with tenants. This study underscores the role of management involvement, organizational readiness, and technical support in successful system integration. The ethnographic approach enriches the analysis by capturing behavioral and cultural dynamics throughout the digital transformation process.